Whither ‘TRS’? - Stringer, Martin D. (Reviews in religion and theology, 2001)
Books reviewed in this article: Willi Braun and Russell T. McCutcheon (eds), Guide to the Study of Religion J'annine Jobling and Ian Markham (eds),Theological Liberalism, Creative and Critical